Integrasi Nilai Tauhid Dan Akhlak Dalam Pembelajaran Di Sekolah Islam - Syamsinar Syamsinar; Husni Mubarak; St. Nurhayati Ali; Muhammad Nur Maallah (Prodi PGSD Unsultra, 2026)
Islamic education aims to shape whole human beings who believe in Allah SWT and have noble morals. However, the reality of modern education shows a tendency to emphasize cognitive aspects that often neglect the spiritual and moral dimensions. Therefore, the integration of the values ​​of monotheism and morals in learning in Islamic schools is an urgent need to realize holistic education. This study aims to examine in depth the concept, strategies, and implications of the integration of the values ​​of monotheism and morals in learning in Islamic schools based on a literature review. The method used is a qualitative approach with a literature study (library research) through an analysis of relevant books and scientific articles published in the last five years. The results of the study indicate that the integration of the values ​​of monotheism and morals is reflected in five main aspects: monotheism as the philosophical foundation of learning, morals as the substantive goal of education, the integration of values ​​in the curriculum and teaching materials, the role of teachers as role models, and school culture as a reinforcement of the internalization of values. This integration of values ​​is able to shape the awareness of God, moral responsibility, and Islamic character of students in a sustainable manner. This study confirms that the integration of the values ​​of monotheism and morals is not merely an additional approach, but rather the core of the Islamic education system. Thus, Islamic schools are expected to consistently implement learning that integrates faith, knowledge, and morals to address the challenges of education in the modern era.